THE EFFECT OF SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) ON ANXIETY AND PAIN IN POST-OPERATIVE FRACTURE PATIENT - Isneini; Nurleli; Hermansyah (Jurnal Ilmiah Keperawatan, 2023)
Postoperative fracture patients can experience anxiety and pain which impact on the healing process because it affects physiological and psychological conditions. Several studies have revealed that this condition can be treated with Spiritual Emotional Freedom Technique (SEFT) therapy because it can eliminate negative emotions. However, the impact on pain and anxiety in postoperative fracture patients who are hospitalized is not yet known. The purpose of this study was to determine the effect of SEFT therapy on reducing anxiety and pain in postoperative fracture patients at dr. Zainoel Abidin (RSUDZA) Banda Aceh. The research method used was quasi-experimental through a post test only control group design by means of randomization of the control and experimental groups, providing educational interventions on SEFT management and post tests on 44 respondents who were divided into the intervention group and the control group. The independent t-test technique obtained  p-value of 0.032 (<0.05) and the Man Whitney U test obtained  p-value of 0.008 (<0.05 so there is a difference between the control group and the control group intervention after being given SEFT therapy. it turns out that the respondent is able to focus attention so as not to experience anxiety which can increase his perception of pain, so that the pain scale decreases. There is a significant effect of SEFT therapy on anxiety and pain in postoperative limb fracture patients. These results are expected to add to the reference to help meet the psychological needs of postoperative fracture patients with pain and anxiety.